Association between social support, smartphone usage and loneliness among the migrant elderly following children in Jinan, China: a cross-sectional study. Issue 5 (24th May 2022) - Liu, Guangwen; Li, Shixue; Kong, Fanlei
Abstract : Objectives: As the fast population ageing in the past few decades, China has also witnessed an increase in the number of migrant elderly following children (MEFC). This study aims to examine the relationship between MEFC's social support, smartphone usage and loneliness in Jinan, China. Design: Cross-sectional survey. Setting: Shandong Province, China. Participants: The participants were 656 MEFC aged 60 years or above. Primary and secondary outcome measures: Loneliness was measured by an eight-item version of the University of California Los Angeles Loneliness Scale (ULS-8). A t-test and one-way Analysis of Variance (ANOVA) were conducted to compare the level of loneliness across different sociodemographic variables, social support indicators and smartphone usage indicators. Structural equation modelling was used to validate the association between the above variables. Results: The MEFC's mean score on the ULS-8 was 12.82±4.05, indicating a relatively lower level of loneliness. It was found that social support and smartphone usage exerted negative effects on loneliness of the MEFC, and the standardised direct effects were −0.165 (95% CI −0.257 to −0.070) and −0.094 (95% CI −0.180 to −0.003), respectively. Social support was found to be positively associated with smartphone usage of the MEFC, and the standardised direct effect was 0.147 (95% CI 0.052 to 0.246). Conclusions: The loneliness of the MEFC was relatively low and was clarified to be negatively associated with social support and smartphone usage. Effective intervention measures on social support and smartphone usage to alleviate loneliness among the MEFC in China were recommended based on this study.